Experimental apparatus for measurement of photoneutrons from linear accelerator with energy of 16 MeV - Marcelo Vilela da Silva; Domingos D'Oliveira Cardoso; Sergio de Oliveira Vellozo (Brazilian Journal of Radiation Sciences, 2021)
Particle accelerator technology has a deep impact on society. Its applications are well established mainly in the treatment of cancer and other diseases. This work aims to develop an experimental apparatus with 3He detectors for 16 MeV photoneutron measurements. The apparatus allows us to obtain multienergetic neutrons with the use of a 22 cm diameter spherical attenuator associated with different shield thicknesses. The microscopic processes of the fast and thermal neutrons in the detector were described by the two energy-group diffusion equation. The Detector Response  Dose Rate results show a directly proportional relationship between these two variables with a degree of reliability attested by the linear correlation coefficient .Particle accelerator technology has a deep impact on society. Its applications are well established mainly in the treatment of cancer and other diseases. This work aims to develop an experimental apparatus with 3He detectors for 16 MeV photoneutron measurements. The apparatus allows us to obtain multienergetic neutrons with the use of a 22 cm diameter spherical attenuator associated with different shield thicknesses. The microscopic processes of the fast and thermal neutrons in the detector were described by the two energy-group diffusion equation. The Detector Response  Dose Rate results show a directly proportional relationship between these two variables with a degree of reliability attested by the linear correlation coefficient .